2017
DOI: 10.1016/j.rse.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

A regional-scale assessment of Himalayan glacial lake changes using satellite observations from 1990 to 2015

Abstract: The Himalaya, the world's highest mountain ranges, are home to a large group of glaciers and glacial lakes. Glacial lake outburst floods (GLOFs) in this region have resulted in catastrophic damages and fatalities in the past decades. The recent warming has caused dramatic glacial lake changes and increased potential GLOFs risk in the Himalaya. However, our knowledge on the current state and change of glacial lakes in the entire Himalaya is limited. This study maps the current (2015) distribution of glacial lak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
279
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 306 publications
(307 citation statements)
references
References 76 publications
(133 reference statements)
21
279
4
3
Order By: Relevance
“…However, these lakes are not larger than 0.1 km 2 nor debris-covered. This is strong evidence for the importance of debris-covered mother glaciers for rapid expansion of large glacial lakes, which is consistent with previous studies [1][2][3]28].…”
Section: Interaction and Integration Of Glof Scale Multiple Indicessupporting
confidence: 92%
See 4 more Smart Citations
“…However, these lakes are not larger than 0.1 km 2 nor debris-covered. This is strong evidence for the importance of debris-covered mother glaciers for rapid expansion of large glacial lakes, which is consistent with previous studies [1][2][3]28].…”
Section: Interaction and Integration Of Glof Scale Multiple Indicessupporting
confidence: 92%
“…They reported that the PRISM DSM used for the ALOS image ortho-rectification had a vertical accuracy of 2.3 ± 7.8 m against ground control points (N = 3268) and a delineated lake outline had a mean distance of 9.5 m (11.7 m in root mean square) from a global positioning system (GPS)-measured outline. It was noted, for the purposes of the current study, that these error values were sufficiently small for delineating lakes >0.01 km 2 .…”
Section: Subsection Completion Of Glacier and Glacial Lake Inventorymentioning
confidence: 69%
See 3 more Smart Citations